Depth-dependent regulation of soil desiccation cracking by geotextiles - Peiyuan Lin; Xun Yuan; Yang Chen; Sheng Li (Geotextiles and Geomembranes, 2026)

Synergistic effects of dimethyl sulfoxide and water in hydrothermal carbonization of poplar form spheric hydrochar with enhanced yields - Haisheng Lin; Mengjiao Fan; Chao Li; Yuchen Jiang; Lijun Zhang; Shu Zhang; Xun Hu (Biomass and Bioenergy, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Rural domestic waste generation characteristics and treatment-related greenhouse gas emissions: A case study of Guangdong Province, China - Yao He; Jie Zhang; Chen Lin; Linlin Xia; Yazhuo Wang; Hewen Zhou; Xun-an Ning (Environmental Pollution, 2026)

A new mode matching criterion for sectional model wind tunnel flutter test of long-span bridges - Hao Zhang; Ming Li; Zhongyu Lin; Hongli Pang; Xun Liang; Mingshui Li (Engineering Structures, 2026)

Single-enzyme-level hierarchical nanohybrids enable spontaneous electron relay, robust enzyme stability, and one-pot sensor printing - Qichao Pan; Yue Lu; Qing Wu; Qingui Yang; Xingyin Zhou; Qingsong Sun; Shouyan Zhang; Wei Wu; Shuhua Zhang; Zhi Geng; Xun Sun; Lin Jia; et al. (Chemical Engineering Journal, 2026)

Early diagenetic dolomitization in methane seep carbonates constrained by coupled Mo and Mg isotopes - Meng Jin; Zice Jia; Jie Li; Xun Sun; Shaomin Lin; Jörn Peckmann; Qinxian Wang; Duofu Chen; Dong Feng (Geochimica et Cosmochimica Acta, 2026)

Dual-domain radio-frequency signal and image joint modeling for coronary calcium detection in intravascular ultrasound - Xu Yu; Yutao Lin; Xun Liu; Shengxian Tu (Medical & Biological Engineering & Computing, 2026)

Multi-measure ecological restoration drives phytoplankton succession and shifts community assembly in an urban eutrophic lake - Xiaowen Lin; Xiaodong Wu; Xuguang Ge; Fan Xun; Weixiang Ren; Mengdie Zhou; Chenxin Zhong; Chunyan Xiao; Linlin Lei (Ecological Engineering, 2026)

Trophic transfer in a cold seep food web: Dual constraints from δ13C-δ15N isotopes and rare earth elements - Zice Jia; Niu Li; Xun Sun; Shamik Dasgupta; Shaomin Lin; Hongfei Lai; Wenhua Feng; Chao Zhong; Zenggui Kuang; Fang Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

A chemical softening–microfiltration platform for simultaneous hardness control and phosphorus fertilizer recovery from agricultural saline-alkaline water - Wuyi Liu; Weifeng Chen; Xun Zhu; Chi Zhang; Enyu Zhang; Viola Somogyi; Zhijun Zhou; Danjun Zheng; Zhikan Yao; Bing Tian; Lin Zhang (Chemical Engineering Journal, 2026)

In vitro regeneration of Lily bulblets and artificial seeds development - Zhengjing Wu; Yuan Long; Luping Cui; Mengting Ma; Xun Liu; Zijing Lin; XinYi Wu; Yifang Su (Journal of Plant Biochemistry and Biotechnology, 2026)

Hydrogeochemical Characteristics and Potential Risks within a Headwater Catchment, Taihu Lake Basin, China - Lin Liu; Hai Yang; Xun Zhou; Yuehua Jiang; Naizheng Xu; Jiangshi Gong; Zi Chen; Liang Li; Jinsong Lü; Yang Jin (Journal of Earth Science, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Reinforced stepwise dissociation of water molecules via U 5f-O 2p-Ti 3d gradient orbital coupling for photoelectrochemical water splitting - Xiaochuan Deng; Tong Liu; Xudong Wu; Qijue Lin; Hanlin Liu; Han Yang; Xun Yang; Maoyin Wang; Kaiguo Chen; Jiayu Dai; Tao Chen; Wenkun Zhu (Science Bulletin, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Diagnosing urban ecological vulnerability in multi-mountainous city from a 3D landscape perspective - Peijia Peng; Xun Lin; Yu Bao (Ecological Engineering, 2026)

Rogue waves in the northern part of the South China Sea: chaotic dynamics and multiparameter synergy determination - Tao Feng; Tianyu Zhang; Danchen Yan; Hailong Wang; Jian Yang; Xun Lin; Junping Zhang (Journal of Oceanology and Limnology, 2026)

Integrated plastic film and straw mulching enhances potato tuber yield in mountainous regions by optimizing rhizospheric metabolites and root–microbe interactions - Kang Du; Xinyue Yang; Zhenpeng Deng; Xi Lin; Mengyuan Hu; Rui Jiang; Guolian Zheng; Xiaoping Yi; Xun Liu; Changwen Lyu; Jichun Wang (Field Crops Research, 2026)

Rab10 GTPase from the mud crab Scylla paramamosain is involved in the host immune response against V. parahaemolyticus infection - Chang-Hong Cheng; Hai-Peng Qin; Si-Gang Fan; Hong-Ling Ma; Guang-Xin Liu; Dong-Lin Yao; Wen-Fan Luo; Xian-Feng Yang; Zhi-Xun Guo (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Retrieving forest LAI from Landsat via 3D look-up table generated by realistic LiDAR scenes - Jianbo Qi; Siying He; Xun Zhao; Su Ye; Tianjia Chu; Zhexiu Yu; Simei Lin; Huaguo Huang (Remote Sensing of Environment, 2026)

SIG-CFFNet: Structural Information-Guided Cascaded Feature Fusion Network for Gastrointestinal Anatomy Classification - Xuli Tan; Xun Gong; Lin Fan; Ting Luo (Annals of Biomedical Engineering, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

High-strength, tear-resistant, and self-damage-reporting elastomers via hydrogen bonding and π-π interactions - Tianping Zhang; Lin Li; Xun Lu (Chemical Engineering Journal, 2026)

A Machine Learning Framework for Drought Prediction in Tropical Malaysia With Input Data Uncertainty - Yi Xun Tan; Jing Lin Ng; Yuk Feng Huang; Norashikin Ahmad Kamal; Ali Najah Ahmed; Majid Mirzaei (International Journal of Climatology, 2026)
The far‐reaching and devastating impacts of drought underscored the need for effective drought forecasting. This study addressed the critical gap of the often‐overlooked impacts of input data uncertainty on the forecasting accuracy. The study incorporated the input data uncertainty as a novel approach into the hybrid Extreme Gradient Boosting‐Recurrent Neural Network (XGBoost‐RNN) to forecast Standardised Precipitation Index (SPI) and Standardised Precipitation Evapotranspiration Index (SPEI) across different time scales in Malaysia. The results were assessed using coefficient of correlation ( R ), root mean square error (RMSE), mean absolute error (MAE), mean square error (MSE), Nash Sutcliffe Efficiency (NSE) and Wilmott's Index (WI). The XGBoost‐RNN incorporating input data uncertainty (XGBoost‐RNN‐ID) outperformed its counterpart, achieving R values up to 0.9988, WI up to 0.9994, and RSME, MAE, and MSE as low as 0.0466, 0.0367, and 0.0022. The NSE values categorised XGBoost‐RNN‐ID as “very good” across all time scales, demonstrating its reliability in drought forecasting.

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Biomass-derived carbon quantum dots in wastewater treatment: Synthesis, sensing, and degradation - Luqiu Lin; Maryam Bayati; Chuxuan Zhang; Huiling Ong; Zhengkang Peng; Xun Gong; Minghou Xu (Journal of Environmental Management, 2026)

Study on the pyrolysis interactions of different anatomical parts of flue-cured tobacco stalks and the catalytic cracking characteristics of nicotine - Jinming Zhang; Guangwei Sun; Luqiu Lin; Zhenguo Chen; Hanwen Nie; Xun Gong (Bioresource Technology, 2026)

Parthenolide Exerts Protection against Hypoxic-Ischemic Brain Damage in Neonatal Rats by Inhibiting Perk-Mediated Endoplasmic Reticulum Stress - Niping Mao; Yihui Zheng; Junhui Yuan; Xiaoli Feng; Yi Ren; Xun Wang; Xiaoyue Tao; Xingyun Wang; Mingchu Fang; Zhenlang Lin (Molecular Neurobiology, 2026)

Inhibition of Neuroinflammation by Costunolide Attenuates Hypoxic-Ischemic Brain Damage via the PI3K/AKT Pathway in Neonatal Rats - Yingying Hu; Rengcheng Qian; Yifeng He; Qiqi Gao; Xun Wang; Huilin Lin; Wei Lin; Yu Fang; Jianghu Zhu; Xingyun Wang; Yan Nan; Zhenlang Lin (Molecular Neurobiology, 2026)

Climate zone governs mercury fate along forest hydrological pathways - Weibin Ma; Jen-How Huang; Gunnar Lischeid; Nantao Liu; Longyu Jia; Fei Wu; Meiqing Sun; Ming Lei; Luxiang Lin; Zhiyun Lu; Wei Yuan; Xun Wang; et al. (Journal of Hazardous Materials, 2025)

Strategies for large-scale preparation of carbon dots and their roles in photocatalytic CO2 reduction: A review - Shujuan Zhang; Xun Gong; Luqiu Lin; Zijian Zhou; Minghou Xu (Journal of Environmental Chemical Engineering, 2025)

Seismic performance of precast concrete shear wall with disc spring-bolt subassembly connections - Hua-long LIU; Xun CHONG; Lin-lin XIE; Qing JIANG; Yu-long FENG; Jun-Qi HUANG (Engineering Structures, 2025)

Enhancing urban thermal resilience in multi-mountainous cities through optimized 3D block morphology: a machine learning framework - Xun Lin; Zhitai Wang; Yu Bao; Xintong Chen (Energy and Buildings, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

Unexpected high prevalence of carbapenemase-producing bacteria and widely spread of blaNDM-1-positive Shewanella spp. in retail shrimp - Chao Yue; Xun Gao; Ludan Xiao; Litao Lu; Jiakuo Chen; Caiying Lin; Zhongpeng Cai; Guolong Gao; Luchao Lv; Jian-Hua Liu; Yi-Yun Liu (International Journal of Food Microbiology, 2025)

The influence of pulsed electric fields with different waveforms on the extraction of valuable compounds from microalgae - Liuxia Li; Yifan Gao; Zihuang Peng; Xun Pei; Ruorong Hua; Fuchang Lin; Rui Zhang; Yi Liu (Innovative Food Science & Emerging Technologies, 2025)

Antilipotoxic framework nucleic acid-loaded injectable hydrogel microspheres for the targeted delivery of miR-34a-5p inhibitors to attenuate dietary fat-associated osteoarthritis - Zhichao Zhang; Liwei Fu; Yazhe Zheng; Jiang Wu; Zhixing Zhang; Chuanyang Long; Xun Yuan; ZhenGang Ding; Xiang Sui; Quanyi Guo; Sirong Shi; Shuyun Liu; et al. (Chemical Engineering Journal, 2025)

Engineered albumin host for ratiometric fluorescent indicator-displacement assay: Distinguishing testosterone from estrone and estradiol - Yuting Luo; Linhui Peng; Zhang Lin; Zhiqing Xun; Na Li; Naiyu Liu; Yalong Wang; Xinfeng Du; Tianyi Qin; Bin Liu; Mingqiang Zhu (Chemical Engineering Journal, 2025)

A Typical Riedel Shear Pattern of Active Faults in the Laolongwan Basin, Northeastern Tibetan Plateau - Kai-Xun Wang; Xiao-Gang Li; Wei Shi; Xiang-You Feng; Qian Yang; Jie Li; Zheng-Jian Xu; Zhou-Jun Peng; Shao-Hua Xu; Yi-Xue Xiong; Mao Lin (Journal of Earth Science, 2025)

Recent advances in bioassays for assessing the toxicity of environmental contaminants in effect-directed analysis - Yao Liu; Minjie Li; Qi-Lin Wan; Xun Wang; Monika Mortimer; Wen-Di Fang; Liang-Hong Guo (Journal of Environmental Sciences, 2025)

Forest and mosaic vegetation cut off savanna corridors during the Last Glacial Maximum in Southeast Asia recorded by marine pollen - Gang Lin; Chuanxiu Luo; Dileep Bandara Herath; Sui Wan; Xiang Su; Yiping Yang; Mingzhen Zhong; Zhiying Wang; Xun Yuan; Rong Xiang (Global and Planetary Change, 2025)

Dual-stage matrix elimination-ICP-MS methodology for REEs profiling in barite-associated ores - Xue-lin Dong; Jun-han Liu; Zheng-xun Jia; Shao-zhan Tang; Shuo-yun Tong; Yu-xiang Xiong; Lei Ouyang (Analytica Chimica Acta, 2025)

Petrogenesis and tectonic implication of the Neoproterozoic Shuimo alkaline-carbonatite complex from Northwestern margin of the Yangtze Block (China) - Bin Lin; Lian-Xun Wang; Yu-Fang Zhong; Xiao-Bing Qi; Xue-Wei Fu; Chang-Qian Ma (Precambrian Research, 2025)

Ecological impacts of treated effluent on multitrophic biodiversity and their interactions - Wei Xiong; Ting Chen; Xun Du; Lin Hou; Yiyong Chen; Jing-Long Han; Aibin Zhan (Environmental Research, 2025)

Delivery of NK cells in an injectable dynamic hydrogel effectively remodels tumor microenvironment and inhibits post-surgery tumor recurrence - Jiaying Long; Yicong Zhang; Mengxing Zhang; Zhenkang Diao; Taotian Zhang; Hanming Zhang; Qing Lin; Tao Gong; Xun Sun; Zhirong Zhang; Shiqi Huang; Ling Zhang (Chemical Engineering Journal, 2025)

Exercise Ameliorates Dysregulated Mitochondrial Fission, Mitochondrial Respiration, and Neuronal Apoptosis in Parkinson’s Disease Mice via the Irisin/AMPK/SIRT1 Pathway - Nan Li; Bin Wang; Yuanxin Wang; Xin Tian; Junjie Lin; Xun Sun; Yu Sun; Xin Zhang; Haocheng Xu; Mingzhi Li; Fanxi Zeng; Renqing Zhao (Molecular Neurobiology, 2025)

Divergence of Two Diospyros Species Promoted by Geo‐Climatic Processes Across Dry Valleys and Lowlands in Subtropical China - Yu‐Juan Zhao; Hui‐Hui Xi; Jiao Lin; Rui Yang; Gen‐Shen Yin; Xun Gong (Journal of Biogeography, 2025)
Aim Exploring the divergence and speciation processes is central to understanding the origin and maintenance of biodiversity. The dry valley mosaic in the Hengduan Mountains and its southern extension range is one of the special landscapes globally and harbours a high level of endemic plants of tropical margin nature. The dry valleys and lowlands‐adapted plants constitute a unique system to explore how the geological and ecological effects have shaped the speciation processes here. Location Subtropical China. Taxon Diospyros dumetorum and Diospyros saxatilis. Methods We surveyed patterns of genetic variation from 33 populations spanning their distribution ranges using three chloroplast DNA fragments and eight nuclear microsatellite loci. Approximate Bayesian computation was conducted to compare population demographic models considering gene flow and to estimate key parameters. We used Ecological Niche Models (ENMs) to reconstruct changes in range distribution during glacial and interglacial periods and evaluate their niche differentiation. Results Plastid and nuclear data strongly support divergence between the two species occurring during the Pliocene/Pleistocene period followed by secondary contact in response to climatic oscillations. ENMs predicted drastic distribution range changes during the Quaternary and identified significant differences in climatic conditions at the set of locations occupied by these two species. Correlation analyses were conducted, and the results suggest that geographical isolation rather than environmental heterogeneity shapes the current population genetic structure within the two species. Main Conclusion Phylogeographical patterns revealed in our results document that geographic vicariance associated with tectonic uplifts initiated allopatric species divergence between the two dry valleys and lowlands‐adapted Diospyros species, and niche differentiation perhaps further accelerated the speciation processes with limited subsequent gene flow. Our findings could contribute to the knowledge of forces that drive speciation processes in the unique landscape of dry valleys, as well as the evolution of the flora in subtropical China.

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Mass transfer analysis of a concentration-regulated metal-assisted chemical etching system and its application in Si nanohole fabrication - Jiecai Long; Xuan Zhang; Haojun Zhang; Haoya Wang; Congkai Xie; Xun Chen; Guohuai Lin; Yun Chen; Xin Chen; Huitao Liu; Renquan Lu (Chemical Engineering Journal, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Analysis of Offshore Pile–Soil Interaction Using Artificial Neural Network - Peiyuan Lin; Kun Li; Xiangwei Yu; Tong Liu; Xun Yuan; Haoyi Li (Journal of Marine Science and Engineering, 2025)
Offshore wind power is one of the primary forms of utilizing marine green energy in China. Currently, near-shore wind power predominantly employs monopile foundations, with designs typically being overly conservative, resulting in high construction costs. Precise characterization of the interaction mechanisms between marine piles and surrounding soils is crucial for foundation design optimization. Traditional p-y curve methods, with simplified fitting functions, inadequately capture the complex pile–soil behaviors, limiting predictive accuracy and model uncertainty quantification. To address these challenges, this research collected 1852 empirical datasets of offshore wind monopile foundation pile–soil interactions, developing p-y curve and horizontal displacement prediction models using artificial neural network (ANN) expressions and comprehensive uncertainty statistical analysis. The constructed ANN model demonstrates a simple structure with satisfactory predictive performance, achieving average error margins below 6% and low to moderate prediction accuracy dispersion (26%~45%). In contrast, traditional p-y curve models show 30%~50% average biases with substantial accuracy dispersion near 80%, while conventional finite element methods exhibit approximately 40% error and dispersion. By strictly characterizing the probability cumulative function of the neural network model factors, a foundation is provided for reliability-based design. Through comprehensive case verification, it is demonstrated that the ANN-based model has significant advantages in terms of computational accuracy and efficiency in the design of offshore wind power foundations.

The tight-coupled SLAM system based on LiDAR and improved VGICP method for waterfront environments - Xun Chen; Yuanguang Lin; Xiaofei Yang; Shang Zhao (Ocean Engineering, 2025)

Potential of submerged macrophytes restoration for reducing CH4 and CO2 emissions in a typical urban lake - Yifan Yin; Zhen Ci; Mengyi Qin; Hanqi Lin; Yiquan Zhang; Fan Xun; Aiyu Xie; Peng Xing; Xinfang Chen; Yaling Su; Muhua Feng (Journal of Environmental Management, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Seeing into individual trees: Tree-specific retrieval of tree-level traits using 3D radiative transfer model and spatial adjacency constraint from UAV multispectral imagery - Linyuan Li; Shangbo Liu; Zhihui Wang; Xun Zhao; Jianbo Qi; Yelu Zeng; Dong Li; Pengfei Guo; Zhexiu Yu; Simei Lin; Shouyang Liu; Huaguo Huang (Remote Sensing of Environment, 2025)

Engineering an Mn(II)-oxidizing Pseudomonas whole-cell catalyst chassis to efficiently biosynthesize 2,5-furandicarboxylic acid from hydroxymethylfurfural - Yongxuan Liu; Zhicheng Zhou; Jingjing Xu; Shiwei Li; Yu Xiao; Xun Yu; Tan Wang; Jie Zeng; Lin Li (Bioresource Technology, 2025)

Efficient photocatalytic CO2 and Cr(VI) reduction on carbon quantum dots/carbon nitride heterojunctions - Zhengdong Xu; Xun Su; Penghui Yang; Junbo Zhong; Minjiao Li; Clemens Burda; Lin Dou (Fuel, 2025)

A trackable mitochondria-targeting nanosystem for mitochondrial redox and mitophagy regulation in diabetic retinopathy management - Yangxue Yao; Xiaoyu Lei; Xun Li; Yichen Ge; Yun Wang; Xin Qin; Yang Gao; Geru Zhang; Yunfeng Lin; Shaojingya Gao; Xiaoxiao Cai (Chemical Engineering Journal, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Harnessing diurnal dynamics: Understanding the influence of light–dark cycle on algal-bacterial symbiotic system under aniline stress - Qi He; Qian Zhang; Meng Li; Jing He; Bing Lin; Nan-Ping Wu; Jia-Jing Chen; Xun-Hao Liu; Xiao-Qian Dong (Bioresource Technology, 2025)

IMST-based identification of time-varying cable forces in cable-supported bridges: Numerical, experimental, and field test validation - Ning Yang; Xun Liu; Peng Huang; Yongbing Huang; Mingqiang Xu; Kaiqi Lin (Ocean Engineering, 2024)

Biodegradation of commercial polyester polyurethane by a soil-borne bacterium Bacillus velezensis MB01B: Efficiency, degradation pathway, and in-situ remediation in landfill soil - Jie Zeng; Junruo Yao; Weiming Zhang; Miaomiao Zhang; Tan Wang; Xun Yu; Yongxuan Liu; Xiaowen Sun; Lin Li (Environmental Pollution, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

The transformation of typical heavy metals during the process for magnetic harvesting and subsequent liquefaction in ethanol of microalgae - Luqiu Lin; Jianhui Zeng; Chuxuan Zhang; Zhengkang Peng; Xun Gong (Algal Research, 2024)

Nitrogen isotope characteristics and importance of NOx from biomass burning in China - Zanfang Jin; Jiawen Li; Qiang Yang; Yasheng Shi; Xun Lin; Fan Chen; Qifang Chen; Zhili Chen; Feili Li (Science of The Total Environment, 2024)

Cyclic di-GMP incorporates the transcriptional factor FleQ03 in Pseudomonas syringae MB03 to elicit biofilm-dependent resistance in response to Caenorhabditis elegans predation - Xiaowen Sun; Fan Xiao; Yuwei Su; Zhi Li; Xun Yu; Rebecca E. Parales; Lin Li (Journal of Invertebrate Pathology, 2024)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Revealing the hidden resource of fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae): Asteraceae weeds as alternative hosts - Yun Hsiao; Feng-Chuan Hsu; You-Ting Hsieh; Wei-Jiun Lin; Xun-Yi Huang; Chuan-Kai Ho (Applied Entomology and Zoology, 2024)

A ConvLSTM nearshore water level prediction model with integrated attention mechanism - Jian Yang; Tianyu Zhang; Junping Zhang; Xun Lin; Hailong Wang; Tao Feng (Frontiers in Marine Science, 2024)
Nearshore water-level prediction has a substantial impact on the daily lives of coastal residents, fishing operations, and disaster prevention and mitigation. Compared to the limitations and high costs of traditional empirical forecasts and numerical models for nearshore water-level prediction, data-driven artificial intelligence methods can more efficiently predict water levels. Attention mechanisms have recently shown great potential in natural language processing and video prediction. Convolutional long short-term memory(ConvLSTM) combines the advantages of convolutional neural networks (CNN) and long short-term Memory (LSTM), enabling more effective data feature extraction. Therefore, this study proposes a ConvLSTM nearshore water level prediction model that incorporates an attention mechanism. The ConvLSTM model extracts multiscale information from historical water levels, and the attention mechanism enhances the importance of key features, thereby improving the prediction accuracy and timeliness. The model structure was determined through experiments and relevant previous studies using five years of water level data from the Zhuhai Tide Station and the surrounding wind speed and rainfall data for training and evaluation. The results indicate that this model outperforms the four other baseline models of PCCs, RMSE, and MAE, effectively predicting future water levels at nearshore stations up to 48 h in advance. Compared to the ConvLSTM model, the model with the attention mechanism showed an average improvement of approximately 10% on the test set, with a greater error reduction in short-term forecasts than that in long-term forecasts. During Typhoon Higos, the model reduced the MAE of the best-performing baseline model by approximately 3.2 and 2.4 cm for the 6- and 24-hour forecasts, respectively, decreasing forecast errors by approximately 18% and 11%, effectively enhancing the ability of the model to forecast storm surges. This method provides a new approach for forecasting nearshore tides and storm surges.

Analysis of two-dimensional consolidation behavior of soils under cyclic loading considering exacerbated tunnel leakage - Sen-Lin Xie; An-Feng Hu; Zhi-Rong Xiao; Mei-Hui Wang; Xun-Jian Hu; Gabriele Della Vecchia; Stefano Mariani (Computers and Geotechnics, 2024)

A tetrahedral framework nucleic acids-based gene therapeutic nanococktail alleviates cartilage damage and protects against osteoarthritis progression - Liwei Fu; Jiang Wu; Sirong Shi; Zhichao Zhang; Yazhe Zheng; Pinxue Li; Xun Yuan; Zhengang Ding; Chao Ning; Xiang Sui; Shuyun Liu; Quanyi Guo; et al. (Chemical Engineering Journal, 2024)

Glutathione‑iron hybrid nanozyme-based colorimetric sensor for specific and stable detection of thiram pesticide on fruit juices - Xu Yan; Ruiqi Zou; Qiqi Lin; Yuan Ma; Aixin Li; Xun Sun; Geyu Lu; Hongxia Li (Food Chemistry, 2024)

Atomically precise gold nanoclusters as ROS-scavenging clusterzymes to treat high-fat diet-induced obesity - Jialuo Ding; Mengyuan Zhao; Yeying Li; Kexin Zhang; Hanxing Chen; Xinying Hu; Le Li; Yu Su; Xun Yuan; Zhenkun Lin (Chemical Engineering Journal, 2024)

Predicting post-fire forest recovery using the 3-PG model with bi-temporal Landsat imagery in high-severity burned areas of Great Xing’an Mountain - Simei Lin; Linyuan Li; Shangbo Liu; Shuo Yang; Danyang Lin; Xun Zhao; Ling Chen; Huaguo Huang (Forest Ecology and Management, 2024)

Stratified burn severity assessment by integrating spaceborne spectral and waveform attributes in Great Xing'an Mountain - Simei Lin; Linyuan Li; Shangbo Liu; Ge Gao; Xun Zhao; Ling Chen; Jianbo Qi; Qin Shen; Huaguo Huang (Remote Sensing of Environment, 2024)

Insight into the synergistic effects of surface microstructures and wall peristalsis on glucose production in a bionic microreactor - Kai Lin; Ao Xia; Yun Huang; Xianqing Zhu; Xun Zhu; Kaiyong Cai; Zidong Wei; Qiang Liao (Chemical Engineering Journal, 2024)

Conditional generation of artificial earthquake waveforms based on adversarial networks - Shieh-Kung Huang; Wei-Ting Chao; Yi-Xun Lin (Soil Dynamics and Earthquake Engineering, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

Numerical simulation and characteristic analysis of flood intrusion into streets and buildings - Yusi Wu; Xun Han; Pengzhi Lin (Journal of Hydrology, 2024)

Formation mechanism of drift-moat contourite systems revealed by in-situ observations in the South China Sea - Yulong Zhao; Zhifei Liu; Yanwei Zhang; Xiaodong Zhang; Pengfei Ma; Xun Yu; Chen Ling; Baozhi Lin; Jingwen Zhang (Earth and Planetary Science Letters, 2024)

Black phosphorus nanosheets inhibit glioblastoma cell migration and invasion through modulation of WNT/β-catenin and NOTCH signaling pathways - Yue Xiong; Chao He; Xun Lin; Ke Cheng; Fumei He; Jingxin Zhao; Mengjie Yang; Hong Gao; Fangjie He; Xiaopei Zhang; Zeqi Liu; Gan Liu; et al. (Chemical Engineering Journal, 2024)

Co-infections of Aeromonas dhakensis and Chryseobacterium indologenes in largemouth bass (Micropterus salmoides) - Qin Yang; Yun-Yao Tu; Na Zhang; Bo Miao; Yu-Zhou Zhang; Xun-Teng Deng; Tao He; Sheng-Qi Su; Ling-Yun Lin; Song Zhu (Aquaculture, 2024)

Abscisic acid promotes selenium absorption, metabolism and toxicity via stress-related phytohormones regulation in Cyphomandra betacea Sendt. (Solanum betaceum Cav.) - Xun Wang; Wen Lu; Ziming Zhao; Wenhui Hao; Ruimin Du; Zhiyu Li; Zhihui Wang; Xiulan Lv; Jin Wang; Dong Liang; Hui Xia; Yi Tang; et al. (Journal of Hazardous Materials, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Estimating leaf age of maize seedlings using UAV-based RGB and multispectral images - Yi Bai; Liangsheng Shi; Yuanyuan Zha; Shuaibing Liu; Chenwei Nie; Honggen Xu; Hongye Yang; Mingchao Shao; Xun Yu; Minghan Cheng; Yadong Liu; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

Effects of solvent phase recycling on microalgae liquefaction in ethanol: Bio-oil production and nitrogen transformation - Chuxuan Zhang; Xun Gong; Jianhui Zeng; Zhengkang Peng; Xiaomin Li; Luqiu Lin; Yang Peng; Shuang Wang (Science of The Total Environment, 2023)

A novel rainfall forecast model using GNSS observations and CAPE - Zhuoya Liu; Yi Wen; Xun Zhang; Mian Wang; Shuzhou Xiao; Yuan Chen; Lin He (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Cover Crops Control Weed and Improve Soil Qualities in Citrus Orchard - Hang Li; Xun Wang; Yuan Li; Yuhui Hou; Ziming Zhao; Lin Meng; Ji Liu; Jun Wang; Bo Xiong; Zhihui Wang (Journal of Soil Science and Plant Nutrition, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Interaction of derivatives of cellulose and lignin in co-HTC, co-pyrolysis and co-activation - Jingyi Liang; Haisheng Lin; Chao Li; Lijun Zhang; Shu Zhang; Shuang Wang; Jun Xiang; Song Hu; Yi Wang; Xun Hu (Fuel, 2023)

Pyrolysis of sawdust impregnated with bio-oil of the same origin: Influence of organics in bio-oil on property of biochar - Zijun Yi; Chao Li; Haisheng Lin; Shu Zhang; Yong Huang; Bin Li; Shuang Wang; Xun Hu (Biomass and Bioenergy, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Reuse of microalgae residue after oil production as a Fenton-like catalyst in wastewater treatment: Catalytic performance and mechanism - Chuxuan Zhang; Jianhui Zeng; Zhipeng Ouyang; Xiaomin Li; Luqiu Lin; Yang Peng; Xun Gong (Journal of Water Process Engineering, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

Drynaria Naringin alleviated mechanical stress deficiency-caused bone loss deterioration via Rspo1/Lgr4-mediated Wnt/β-catenin signalling pathway - Gui-Xun Shi; Wei-Dong Sun; Zeng-Huan Chen; Chuan-Jun Yang; Wang-Lin Luo; Dan-Feng Wang; Ze-Zhu Zhou (In Vitro Cellular & Developmental Biology - Animal, 2023)

Quantitative analysis of input data uncertainty for SPI and SPEI in Peninsular Malaysia based on the bootstrap method - Yi Xun Tan; Jing Lin Ng; Yuk Feng Huang (Hydrological Sciences Journal, 2023)

Polyphenolic glycosides with unusual four-membered ring possessing anti-Parkinson's disease potential from black wolfberry - Yi-Kao Hu; Xiao-Lin Bai; Guang-Yu Shi; Yong-Mei Zhang; Xun Liao (Phytochemistry, 2023)

Quantifying effect of maize tassels on LAI estimation based on multispectral imagery and machine learning methods - Mingchao Shao; Chenwei Nie; Aijun Zhang; Liangsheng Shi; Yuanyuan Zha; Honggen Xu; Hongye Yang; Xun Yu; Yi Bai; Shuaibing Liu; Minghan Cheng; Tao Lin; et al. (Computers and Electronics in Agriculture, 2023)

Complete oxidative degradation of diclofenac via coupling free radicals and oxygenases of a micro/nanostructured biogenic Mn oxide composite from engineered Pseudomonas sp. MB04R-2 - Yongxuan Liu; Jiaoqing Li; Jie Zeng; Xun Yu; Xiaowen Sun; Zhicheng Zhou; Jingjing Xu; Liangzheng Xu; Lin Li (Journal of Hazardous Materials, 2023)

A sustainable emulsion for separation and Raman identification of microplastics and nanoplastics - Yinan Li; Jianxin Fu; Lin Peng; Xun Sun; Guoqing Wang; Yunqing Wang; Lingxin Chen (Chemical Engineering Journal, 2023)

Evaluation of alternative processes of methanol production from CO2: Design, optimization, control, techno-economic, and environmental analysis - Hsuan-Han Chiou; Chi-Jui Lee; Bo-Sheng Wen; Jian-Xun Lin; Cheng-Liang Chen; Bor-Yih Yu (Fuel, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

TiO2/g-C3N4 photoanode prepared with polydopamine inspiration for photocatalytic fuel cells towards simultaneous wastewater treatment and electricity generation - Yuxin Liu; Lin Chen; Jinwang Li; Rong Chen; Xun Zhu; Dingding Ye; Yang Yang; Qiang Liao (Journal of Water Process Engineering, 2023)

First detection of tet(X4)-positive Enterobacterales in retail vegetables and clonal spread of Escherichia coli ST195 producing Tet(X4) in animals, foods, and humans across China and Thailand - Chao Yue; Xun Gao; Litao Lu; Yi-Yun Liu; Lu-Chao Lv; Xiaotong He; Guolong Gao; Yanxiang Jiao; Huiying Yue; Wannan Lin; Jian-Hua Liu (International Journal of Food Microbiology, 2023)

Unraveling the role of chemical composition in the critical cooling rate of high-temperature CMAS slag - Junjun Wu; Bin Lin; Hong Wang; Xun Zhu; Qiang Liao (Fuel, 2023)

Enhanced adsorption of bio-oil on activated biochar in slurry fuels and the adsorption selectivity - Shanshan Yan; Haoran Chen; Haonan Zhu; Zixiang Lin; Gang Wu; Wenran Gao; Hong Zhang; Xun Hu; Junjie Zhang; Shu Zhang; Shoujun Zhang; Yinlong Wu (Fuel, 2023)

How can vanillin improve the performance of lignocellulosic biomass conversion in an immobilized laccase microreactor system? - Kai Lin; Ao Xia; Yun Huang; Xianqing Zhu; Xun Zhu; Kaiyong Cai; Zidong Wei; Qiang Liao (Bioresource Technology, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Yield gap of rice genotypes under N and P deficiencies: Evidence from differential recruitment of bacterial keystone taxa in the rhizosphere - Jia Lin Wang; Xun Xiao; An Yong Hu; Ren Fang Shen; Xue Qiang Zhao (Applied Soil Ecology, 2023)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

MiR-29a-3p inhibits high-grade transformation and epithelial–mesenchymal transition of lacrimal gland adenoid cystic carcinoma by targeting Quaking - Fei Xu; Meixia Jiang; Qin Tang; Jiaqi Lin; Xun Liu; Chuanli Zhang; Jinzhi Zhao; Yanjin He; Lijie Dong; Limin Zhu; Tingting Lin (Molecular Biology Reports, 2023)

Aluminum-Tolerant Wheat Genotype Changes Root Microbial Taxa and Nitrogen Uptake According to Soil pH Levels and Nitrogen Rates - Xin Jun Dai; Jia Lin Wang; Xun Xiao; Xiao Ying Dong; Ren Fang Shen; Xue Qiang Zhao (Journal of Soil Science and Plant Nutrition, 2023)

Rising temperatures affect the interspecific interference competition between Harmonia axyridis and Propylea japonica, and their predation rate on Myzus persicae - Xing-Lin Yu; Yu-Jie Zhang; Jun-Feng Zuo; Xun Luo; Long Zhang; Zhuo-Ma Danzeng; Bo Wang; Peng-Liang Xia; Shi-Ze Zhang; Tong-Xian Liu; Yi Feng (Journal of Pest Science, 2023)

Spatiotemporal variability assessment and accuracy evaluation of Standardized Precipitation Index and Standardized Precipitation Evapotranspiration Index in Malaysia - Yi Xun Tan; Jing Lin Ng; Yuk Feng Huang (Earth Science Informatics, 2023)

3D numerical study of splitter Plate's effect on a flexible cylinder VIV - He Liu; Xun Han; J.J.R. Williams; Runyu Xie; Pengzhi Lin (Ocean Engineering, 2023)

Experimental study on 3D source localization in indoor environments with weak airflow based on two bionic swarm intelligence algorithms - Axiang Chen; Yu Liao; Hao Cai; Xun Guo; Boyuan Zhang; Bencheng Lin; Wei Zhang; Ling Wei; Yan Tong (Building and Environment, 2023)

RBM3 interacts with Raptor to regulate autophagy and protect cardiomyocytes from ischemia–reperfusion-induced injury - Nan Wang; Limeiting Wang; Changyan Li; Peng Rao; Xun Wang; Yazhou Xu; Lin Yang; Lin Sun; Di Lu (Journal of Physiology and Biochemistry, 2023)

Effects of dietary sodium acetate on intestinal health of juvenile Trachinotus ovatus based on multi-omics approach - Pengwei Xun; Chuanpeng Zhou; Xiaolin Huang; Zhong Huang; Wei Yu; Yukai Yang; Jianbin Huang; Yang Wu; Ruixuan Wang; Heizhao Lin (Aquaculture, 2023)

Black phosphorus nanosheets suppress oxidative damage of stem cells for improved neurological recovery - Fumei He; Zeqi Liu; Jian Xu; Yue Xiong; Xiaopei Zhang; Junyang Qi; Xun Lin; Chengjun Chu; Lan Shen; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Carotenoid components and their biosynthesis in a bud mutant of Shiranui mandarin (Citrus reticulata Blanco) with citrine flavedo - Xun Wang; Jinqiu Huang; Zongyan Yin; Ke Xu; Dong Jiang; Lijin Lin; Xiaoai Zhang; Zhihui Wang (Journal of Zhejiang University-SCIENCE B, 2023)

Characterising the influence of acid rain on the growth and physiological characteristics of Mirabilis jalapa Linn. in southern China - Lan-ying Chen; Lin Wang; Hao-yu Wang; Xun Zhu (Acta Physiologiae Plantarum, 2023)

Mercury cycling and isotopic fractionation in global forests - Xun Wang; Wei Yuan; Che-Jen Lin; Xinbin Feng (Critical Reviews in Environmental Science and Technology, 2022)

Identification of a 5-gene-risk score model for predicting luminal A-invasive lobular breast cancer survival - Yi-Huan Chen; Tao-Feng Zhang; Yi-Yuan Liu; Jie-Hua Zheng; Wei-Xun Lin; Yao-Kun Chen; Jie-Hui Cai; Juan Zou; Zhi-Yang Li (Genetica, 2022)

RsmA3 modulates RpoS through the RetS‐Gac‐Rsm signalling pathway in response to H 2 O 2 stress in the phytopathogen Pseudomonas syringae - Xun Yu; Cui Meng; Xiaocheng Tan; Yuwei Su; Zhiping Cao; Tzann‐Shun Hwang; Lin Li (Environmental Microbiology, 2022)
Reactive oxygen species are a fatal challenge to the plant pathogenic bacterium Pseudomonas syringae . In this study, we reveal that the global regulatory protein RsmA3 from the RetS‐Gac/Rsm signalling pathway modulates RpoS in the early‐log growth phase in the P . syringae wild‐type strain MB03, thereby regulating oxidative tolerance to H 2 O 2 and ultimately affecting pathogenicity to the host plant. Following increased H 2 O 2 by external addition or endogenous induction by menadione, the resistance of the mutant strain Δ retS to H 2 O 2 is significantly enhanced due to rapid increases in the transcription of Rsm‐related non‐coding small RNAs (nc sRNAs), a sigma factor RpoS, and H 2 O 2 ‐detoxifying enzymes. Moreover, the Δ retS mutant is significantly less pathogenic in cucumber leaves. Seven Rsm‐related nc sRNAs (namely, rsmZ , rsmY and rsmX 1–5 ) show functional redundancy in the RetS‐Gac‐Rsm signalling pathway. External addition of H 2 O 2 stimulates increases in the transcription of both rsmY and rsmZ . Thus, we propose a regulatory model of the RetS‐Gac‐Rsm signalling pathway in P . syringae MB03 for the regulation of H 2 O 2 tolerance and phytopathogenicity in the host plant.

Paleo-karst zone and its control on reservoirs in the fourth member of the Sinian Dengying formation in the Moxi area, central Sichuan Basin - Qinyu Xia; Haijun Yan; Wei Xu; Lin Zhang; Qian Li; Wenjun Luo; Hui Deng; Xun Zhu; Xinyu Li; Jichen Yu (Carbonates and Evaporites, 2022)

Characteristics and changes of the Himalayas glacial area in China during 1990–2015 - Shu-xian Shi; Li Xing; Yue-kai Ding; Jun Dong; Rui Liu; Qin Ji; Zuo-lin Xiao; Xun Huang (Journal of Mountain Science, 2022)

Investigation on grouting diffusion in inclined fracture with flowing water conditions - Jia-fan Zhang; Xun-xun Chen; Yang Liu; Hui-mei Zhang; Chun-lin Wang; Gang Fang (Arabian Journal of Geosciences, 2022)

Aquimarina algicola sp. nov., isolated from the surface of a marine red alga - Xun-Ke Sun; Yan-Lin Zhong; Xu-Yang Chen; Guan-Jun Chen; Zong-Jun Du (Archives of Microbiology, 2021)

Rapid transition from MORB-type to SSZ-type oceanic crust generation following subduction initiation: insights from the mafic dikes and metamorphic soles in the Pozantı-Karsantı ophiolite, SE Turkey - Guang-Yao Xin; Yang Chu; Ben-Xun Su; Wei Lin; Ibrahim Uysal; Zhen-Tian Feng (Contributions to Mineralogy and Petrology, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

Increased EZH2 Levels in Anterior Cingulate Cortex Microglia Aggravate Neuropathic Pain by Inhibiting Autophagy Following Brachial Plexus Avulsion in Rats - Xiang-Lei Meng; Pengfei Fu; Lin Wang; Xun Yang; Guanghui Hong; Xin Zhao; Jie Lao (Neuroscience Bulletin, 2020)

Potential Genes Related to Levofloxacin Resistance in Mycobacterium tuberculosis Based on Transcriptome and Methylome Overlap Analysis - Hai-cheng Li; Hui-xin Guo; Tao Chen; Wei Wang; Zhu-hua Wu; Liang Chen; Hui-zhong Wu; Gao-po Xu; Xun-xun Chen; Lin Zhou (Journal of Molecular Evolution, 2020)
Drug-resistant Mycobacterium tuberculosis ( M. tuberculosis ) has become an increasingly serious public health problem and has complicated tuberculosis (TB) treatment. Levofloxacin (LOF) is an ideal anti-tuberculosis drug in clinical applications. However, the detailed molecular mechanisms of LOF-resistant M. tuberculosis in TB treatment have not been revealed. Our study performed transcriptome and methylome sequencing to investigate the potential biological characteristics of LOF resistance in M. tuberculosis H37Rv. In the transcriptome analysis, 953 differentially expressed genes (DEGs) were identified; 514 and 439 DEGs were significantly downregulated and upregulated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 97 pathways were enriched in this study. In the methylome analysis, 239 differentially methylated genes (DMGs) were identified; 150 and 89 DMGs were hypomethylated and hypermethylated in the LOF-resistant group and control group, respectively. The KEGG pathway analysis revealed that 74 pathways were enriched in this study. The overlap study suggested that 25 genes were obtained. It was notable that nine genes expressed downregulated mRNA and upregulated methylated levels, including pgi , fadE4 , php , cyp132 , pckA , rpmB1 , pfkB , acg , and ctpF , especially cyp132 , pckA , and pfkB , which were vital in LOF-resistant M. tuberculosis H37Rv. The overlapping genes between transcriptome and methylome could be essential for studying the molecular mechanisms of LOF-resistant M. tuberculosis H37Rv. These results may provide informative evidence for TB treatment with LOF.

Characterization and fine mapping of qkrnw4, a major QTL controlling kernel row number in maize - Ningning Nie; Xiaoyu Ding; Lin Chen; Xun Wu; Yixin An; Chunhui Li; Yanchun Song; Dengfeng Zhang; Zhizhai Liu; Tianyu Wang; Yu Li; Yong-xiang Li; et al. (Theoretical and Applied Genetics, 2019)

Effects of mutual grafting on cadmium accumulation characteristics of first post-generations of Bidens pilosa L. and Galinsoga parviflora Cav. - Hongyan Li; Jin Wang; Lijin Lin; Ming’an Liao; Xiulan Lv; Yi Tang; Xun Wang; Hui Xia; Dong Liang; Wei Ren; Wei Jiang (Environmental Science and Pollution Research, 2019)

Effects of self-rooted grafting on growth and cadmium accumulation in post-grafting generations of soybean (Glycine max) - Jin Wang; Huan Yao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Xiulan Lv; Ming’an Liao; Guochao Sun; Huanxiu Li; Xun Wang; Wei Ren (Environmental Monitoring and Assessment, 2019)

Extensive changes in gene expression and alternative splicing due to homoeologous exchange in rice segmental allopolyploids - Zhibin Zhang; Tiansi Fu; Zhijian Liu; Xutong Wang; Hongwei Xun; Guo Li; Baoxu Ding; Yuzhu Dong; Xiuyun Lin; Karen A. Sanguinet; Bao Liu; Ying Wu; et al. (Theoretical and Applied Genetics, 2019)

Age-Related Reduction in Cortical Thickness in First-Episode Treatment-Naïve Patients with Schizophrenia - Yin Lin; Mingli Li; Yi Zhou; Wei Deng; Xiaohong Ma; Qiang Wang; Wanjun Guo; Yinfei Li; Lijun Jiang; Xun Hu; Nanyin Zhang; Tao Li (Neuroscience Bulletin, 2019)

Effects of intercropping with floricultural accumulator plants on cadmium accumulation in grapevine - Hongqiang Chen; Lijin Lin; Ming’an Liao; Jin Wang; Yi Tang; Guochao Sun; Dong Liang; Hui Xia; Qunxian Deng; Xun Wang; Xiulan Lv; Wei Ren (Environmental Science and Pollution Research, 2019)

Design, synthesis and biological evaluation of novel indone derivatives as selective ERβ modulators - Xi-Xi Liu; Mei-Lin Tang; Chen Zhong; Yun Tang; Jian-Ming Yu; Xun Sun (Medicinal Chemistry Research, 2019)

Synthesis and antiphytoviral activity of α-aminophosphonates containing 3, 5-diphenyl-2-isoxazoline as potential papaya ringspot virus inhibitors - Zhi-Gang Zeng; Niu Liu; Fei Lin; Xun-Yuan Jiang; Han-Hong Xu (Molecular Diversity, 2019)

Cutting after grafting affects the growth and cadmium accumulation of Nasturtium officinale - Xingyu Zhang; Fenqin Zhang; Jin Wang; Lijin Lin; Ming’an Liao; Yi Tang; Guochao Sun; Xun Wang; Xiulan Lv; Qunxian Deng; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

Phytoremediation potential of Pterocypsela laciniata as a cadmium hyperaccumulator - Lisha Zhong; Lijin Lin; Ming’an Liao; Jin Wang; Yi Tang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; Huifen Zhang; Wei Ren (Environmental Science and Pollution Research, 2019)

Comparison of Inorganic and Organically Bound Trace Minerals on Tissue Mineral Deposition and Fecal Excretion in Broiler Breeders - Geng Wang; Lujie Liu; Zhongpei Wang; Xun Pei; Wenjing Tao; Zhiping Xiao; Bojing Liu; Minqi Wang; Gang Lin; Tuoying Ao (Biological Trace Element Research, 2019)

Magma–magma interaction in the mantle recorded by megacrysts from Cenozoic basalts in eastern China - Xun Yu; Gang Zeng; Li-Hui Chen; Sen-Lin Hu; Zhi-Qiang Yu (International Geology Review, 2019)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

Cadmium-accumulator straw application alleviates cadmium stress of lettuce (Lactuca sativa) by promoting photosynthetic activity and antioxidative enzyme activities - Yi Tang; Yongdong Xie; Guochao Sun; Huaqiang Tan; Lijin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Xiulan Lv; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2018)

Combined ultrasound with Fenton treatment for the degradation of carcinogenic polycyclic aromatic hydrocarbons in textile dying sludge - Jian-Hao Zhang; Hai-Yuan Zou; Xun-An Ning; Mei-Qing Lin; Chang-Min Chen; Tai-Cheng An; Jian Sun (Environmental Geochemistry and Health, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Effects of melatonin on the growth and cadmium characteristics of Cyphomandra betacea seedlings - Lijin Lin; Jianhua Li; Fabo Chen; Ming’an Liao; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2018)

Characterization and fine mapping of qkc7.03: a major locus for kernel cracking in maize - Mingtao Yang; Lin Chen; Xun Wu; Xing Gao; Chunhui Li; Yanchun Song; Dengfeng Zhang; Yunsu Shi; Yu Li; Yong-xiang Li; Tianyu Wang (Theoretical and Applied Genetics, 2018)

Expression profiles of microRNAs in oxidized low-density lipoprotein-stimulated RAW 264.7 cells - Xiaokai Li; Siyuan Feng; Yi Luo; Keren Long; Zhenghao Lin; Jideng Ma; Anan Jiang; Long Jin; Qianzi Tang; Mingzhou Li; Xun Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Effects of mutual intercropping on the cadmium accumulation in accumulator plants Stellaria media, Malachium aquaticum, and Galium aparine - Qiyu Lu; Jianhua Li; Fabo Chen; Ming’an Liao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of live Myriophyllum aquaticum and its straw on cadmium accumulation in Nasturtium officinale - Kewen Huang; Lijin Lin; Fabo Chen; Ming’an Liao; Jin Wang; Yi Tang; Yunsong Lai; Dong Liang; Hui Xia; Xun Wang; Wei Ren (Environmental Science and Pollution Research, 2017)

Hyperaccumulator straw improves the cadmium phytoextraction efficiency of emergent plant Nasturtium officinale - Keqiang Li; Lijin Lin; Jin Wang; Hui Xia; Dong Liang; Xun Wang; Ming’an Liao; Li Wang; Li Liu; Cheng Chen; Yi Tang (Environmental Monitoring and Assessment, 2017)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

Quantification of mycotoxins in vegetable oil by UPLC-MS/MS after magnetic solid-phase extraction - Yan Zhao; Li-Hong Wan; Xiao-Lin Bai; Yi-Ming Liu; Feng-Ping Zhang; Yao-Min Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

A novel beta-galactose-specific lectin of the tubeworm, Ridgeia piscesae, from the hydrothermal vent - Lingwei Ruan; Haipeng Xu; Wenyang Lin; Hong Shi; Zhizhong Cui; Xun Xu (Acta Oceanologica Sinica, 2017)

Addition of straw from hyperaccumulator plants to cadmium-contaminated soil increases cadmium uptake by loquat seedlings - Lijin Lin; Ming’an Liao; Xiulan Lv; Dong Liang; Hui Xia; Jin Wang; Xun Wang (Environmental Monitoring and Assessment, 2017)

Rapid determination of gizzerosine in fish meals using microchip capillary electrophoresis with laser-induced fluorescence detection - Meng-Wei Xiao; Xiao-Lin Bai; Pei-Li Xu; Yan Zhao; Li Yang; Yi-Ming Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

Cellulase with high β-glucosidase activity by Penicillium oxalicum under solid state fermentation and its use in hydrolysis of cassava residue - Lin-Hui Su; Shuai Zhao; Sui-Xin Jiang; Xu-Zhong Liao; Cheng-Jie Duan; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Both major and minor QTL associated with plant height can be identified using near-isogenic lines in maize - Xiaoyu Ding; Xun Wu; Lin Chen; Chunhui Li; Yunsu Shi; Yanchun Song; Dengfeng Zhang; Tianyu Wang; Yu Li; Zhizhai Liu; Yong-xiang Li (Euphytica, 2017)

Cadmium accumulation characteristics of F1 hybrids by reciprocal hybridizing of Solanum nigrum in two climate–ecology regions - Lijin Lin; Jing He; Xun Wang; Jin Wang; Xiulan Lv; Ming’an Liao; Zhihui Wang; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai (Environmental Science and Pollution Research, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Fine mapping of qKW7, a major QTL for kernel weight and kernel width in maize, confirmed by the combined analytic approaches of linkage and association analysis - Xin Li; Yong-xiang Li; Lin Chen; Xun Wu; Weiwei Qin; Yanchun Song; Dengfeng Zhang; Tianyu Wang; Yu Li; Yunsu Shi (Euphytica, 2016)

Effects of seasonal variations on soil microbial community composition of two typical zonal vegetation types in the Wuyi Mountains - Ze-yan Wu; Wen-xiong Lin; Jian-juan Li; Jin-fu Liu; Bai-lian Li; Lin-kun Wu; Chang-xun Fang; Zhi-xing Zhang (Journal of Mountain Science, 2016)

Lasiodiplodins from mangrove endophytic fungus Lasiodiplodia sp. 318# - Jing Li; Yanyu Xue; Jie Yuan; Yongjun Lu; Xun Zhu; Yongcheng Lin; Lan Liu (Natural Product Research, 2016)

The effects of abscisic acid (ABA) addition on cadmium accumulation of two ecotypes of Solanum photeinocarpum - Jin Wang; Lijin Lin; Li Luo; Ming’an Liao; Xiulan Lv; Zhihui Wang; Dong Liang; Hui Xia; Xun Wang; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

Effects of grafting on the cadmium accumulation characteristics of the potential Cd-hyperaccumulator Solanum photeinocarpum - Lijin Lin; Daiyu Yang; Xun Wang; Ming’an Liao; Zhihui Wang; Xiulan Lv; Fuyi Tang; Dong Liang; Hui Xia; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

Exome sequencing identified FGF12 as a novel candidate gene for Kashin-Beck disease - Feng Zhang; Lanlan Dai; Weimin Lin; Wenyu Wang; Xuanzhu Liu; Jianguo Zhang; Tielin Yang; Xiaogang Liu; Hui Shen; Xiangding Chen; Lijun Tan; Qing Tian; et al. (Functional & Integrative Genomics, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Upregulation of centromere protein H is associated with progression of renal cell carcinoma - Xun Wu; Youcheng Lin; Liping Shi; Yi Huang; Caiyong Lai; Yongqiang Wang; Meng Zhang; Shupeng Wang; Baoli Heng; Ganshen Yu; Xinghua Du; Lu Fang; et al. (Journal of Molecular Histology, 2015)

Two new macrosporin dimers from the fungus Alternaria sp. XZSBG-1 - Bin Chen; Lan Liu; Xun Zhu; Jun Wang; Yi Long; Si-Ping Jiang; Ai-Guo Xu; Yong-Cheng Lin (Natural Product Research, 2015)

Genome-Wide Identification of microRNAs and Their Targets in Cold-Stored Potato Tubers by Deep Sequencing and Degradome Analysis - Yongbin Ou; Xun Liu; Conghua Xie; Huiling Zhang; Yuan Lin; Meng Li; Botao Song; Jun Liu (Plant Molecular Biology Reporter, 2015)

Rifampicin Loaded Mannosylated Cationic Nanostructured Lipid Carriers for Alveolar Macrophage-specific Delivery - Xu Song; Qing Lin; Ling Guo; Yao Fu; Jianfeng Han; Huan Ke; Xun Sun; Tao Gong; Zhirong Zhang (Pharmaceutical Research, 2015)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

The phosphorylation of an actin depolymerizing factor by a calcium-dependent protein kinase regulates cotton fiber elongation - Quan-Sheng Huang; Xun-Ji Chen; Jian-Ping Li; Xiao-Yan Hao; Guo Chen; Zumuremu; Lin Shao (Acta Physiologiae Plantarum, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Genes in the serotonin pathway are associated with bipolar affective disorder in a Han Chinese population - Bo Xiang; Zhenxing Yang; Yin Lin; Lijie Guan; Xuan Li; Wei Deng; Zeyu Jiang; Guohui Lao; Qiang Wang; Xiaoyu Hao; Xiang Liu; Yingcheng Wang; et al. (Neuroscience Bulletin, 2014)

The Role of Pentacyclic Triterpenoids in the Allelopathic Effects of Alstonia scholaris - Chao-Min Wang; Hsiao-Ting Chen; Tsai-Chi Li; Jen-Hsien Weng; Yun-Lian Jhan; Shi-Xun Lin; Chang-Hung Chou (Journal of Chemical Ecology, 2014)

Quantitative changes of nitrergic neurons during postnatal development of chicken myenteric plexus - Ping Yang; Jameel Ahmed Gandahi; Qian Zhang; Lin-li Zhang; Xun-guang Bian; Li Wu; Yi Liu; Qiu-sheng Chen (Journal of Zhejiang University-SCIENCE B, 2013)

Profiling of StvacINV1 Expression in Relation to Acid Invertase Activity and Sugar Accumulation in Potato Cold-Stored Tubers - Yongbin Ou; Botao Song; Xun Liu; Yuan Lin; Huiling Zhang; Meng Li; Hui Fang; Jun Liu (Potato Research, 2013)

Effect of Arborvitae Seed on Cognitive Function and α7nAChR Protein Expression of Hippocampus in Model Rats with Alzheimer’s Disease - Xiang-lin Cheng; Xun-bo Xiong; Ming-qing Xiang (Cell Biochemistry and Biophysics, 2013)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Development of a core set of single-locus SSR markers for allotetraploid rapeseed (Brassica napus L.) - Haitao Li; Muhammad Younas; Xiaofeng Wang; Xuemin Li; Lin Chen; Bo Zhao; Xun Chen; Jinsong Xu; Fan Hou; Baohua Hong; Gang Liu; Hongyang Zhao; et al. (Theoretical and Applied Genetics, 2013)

Reproductive hormones and interleukin-6 in serious leisure male athletes - Leah Z. FitzGerald; Wendie A. Robbins; James S. Kesner; Lin Xun (European Journal of Applied Physiology, 2012)

Spatio-temporal variability of streamflow in the Yellow River: possible causes and implications - Chi Yuan Miao; Wen Shi; Xun Hong Chen; Lin Yang (Hydrological Sciences Journal, 2012)

Simvastatin protects osteoblast against H2O2-induced oxidative damage via inhibiting the upregulation of Nox4 - Wei Huang; Wei-lin Shang; De-hao Li; Wen-wen Wu; Shu-xun Hou (Molecular and Cellular Biochemistry, 2012)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Systematic analysis of potato acid invertase genes reveals that a cold-responsive member, StvacINV1, regulates cold-induced sweetening of tubers - Xun Liu; Chi Zhang; Yongbin Ou; Yuan Lin; Botao Song; Conghua Xie; Jun Liu; Xiu-Qing Li (Molecular Genetics and Genomics, 2011)

A Proteomic Analysis of Leaf Responses to Enhanced Ultraviolet-B Radiation in Two Rice (Oryza sativa L.) Cultivars Differing in UV Sensitivity - Xing-Chun Wu; Chang-Xun Fang; Jin-Yang Chen; Qing-Shui Wang; Ting Chen; Wen-Xiong Lin; Zhong-Liang Huang (Journal of Plant Biology, 2011)

Population structure of Nouelia insignis (Asteraceae), an endangered species in southwestern China, based on chloroplast DNA sequences: recent demographic shrinking - Xun Gong; Shan-Shan Luan; Kuo-Hsiang Hung; Chi-Chuan Hwang; Chung-Jean Lin; Yu-Chung Chiang; Tzen-Yuh Chiang (Journal of Plant Research, 2011)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Automatic Removal of Eye-Movement and Blink Artifacts from EEG Signals - Jun Feng Gao; Yong Yang; Pan Lin; Pei Wang; Chong Xun Zheng (Brain Topography, 2010)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Positive correlation between soil bacterial metabolic and plant species diversity and bacterial and fungal diversity in a vegetation succession on Karst - Xun-Yang He; Ke-Lin Wang; Wei Zhang; Zhi-Hui Chen; Yong-Guan Zhu; Hong-Song Chen (Plant and Soil, 2008)

A rice transcription factor OsbHLH1 is involved in cold stress response - Yu-Jun Wang; Zhi-Gang Zhang; Xin-Jian He; Hua-Lin Zhou; Yu-Xiang Wen; Ji-Xun Dai; Jin-Song Zhang; Shou-Yi Chen (Theoretical and Applied Genetics, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)